Loess Plateau check dams can potentially sequester eroded soil organic carbon. Issue 6 (9th June 2016) - Zhang, Haicheng; Liu, Shuguang; Yuan, Wenping; Dong, Wenjie; Xia, Jiangzhou; Cao, Yaojun; Jia, Yanwei
Abstract: Check dams are special soil and water conservation structures in the Loess Plateau, China. They play an important role in intercepting sediments and soil organic carbon (SOC). However, the decomposition of intercepted SOC and the environmental regulations at check dams have not been investigated. We conducted several paired field experiments at both check dams and slope lands in the Yanhe Watershed of the Loess Plateau to examine the characteristics of SOC decomposition at check dams. On average, the SOC mineralization rate in slope lands was approximately three times higher than in check dams. Increased soil moisture and compaction in check dams can constrain carbon mineralization by limiting the oxygen availability of SOC and can isolate substrate carbon from heterotrophic microorganisms. Our results indicate that check dams display a considerable potential for eroded SOC sequestration via reducing the soil respiration rate and highlight the important implications of lateral carbon redistribution and human engineering projects when estimating regional or global ecosystem carbon cycles. Key Points: Soil erosion can alter both lateral movements and vertical fluxes of soil carbon Check dams in Loess Plateau can increase land carbon sink Soil erosion and check dams change ecosystem carbon flux by altering soil moisture and properties